A GOIABEIRA E OS ARAÃ‡ÃZEIROS DESCRITOS POR PISO E MARCGRAV NO SÃ‰CULO 17, DO NORDESTE - Pickel, D. Bento (REVISTA DE AGRICULTURA, 2016)
A GOIABEIRA E OS ARAÃ‡ÃZEIROS DESCRITOS POR PISO E MARCGRAV NO SÃ‰CULO 17, DO NORDESTE